Shifting the Balance : Obama and the Americas - Whitehead, Laurence; Piccone, Theodore J.; Lowenthal, Abraham F. (Book collections on Project MUSE., 2011)
"Examines the successful and unsuccessful approaches to rapprochement between the United States and various countries in Latin America and the Caribbean after the first year of the Obama administration against a background of initial optimism giving way to both U.S. and Latin American domestic political realities"--Provided by publisher.